1999
DOI: 10.1111/j.1745-4514.1999.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF PEROXIDASES FROM BARLEY KERNEL (Hordeum vulgare L.) AND WHEAT GERM (Triticum aestivum L.): ISOLATION AND PRELIMINARY CHARACTERIZATION

Abstract: Peroxidases (POD) of crude extracts from barley and wheat germ were separated, partially purified using salt fractionation, ion-exchange and hydrophobic interaction chromatographies and their properties examined. Barley and wheat germ POD contained basic, neutral and anionic isoforms as confirmed by isoelectric focusing. Toyopearl-Bug1 650 M chromatography resolved POD into four cationic fractions. Chromatography of wheat germ extract on CM-Sepharose isolated an anionic and a neutral @action. Following chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…The pH optima cPOD-I and rPOD-II were therefore thought to be suitable for the environment in which they are localized. Our result was nearly similar to that reported for POD isoenzymes in Korean radish at pH 5.0 and 6.5 [48] and wheat germ at pH 5.3 and 6.3 [65] but slightly higher than POD in potato tuber sprouts at 4.0 [52], red pepper at 4.5 [66], marula fruit at 4.0 [67], and broccoli at pH 4.0 [4]. However, Lopez and Burgos [68] reported that the release of the heme group from the enzyme active site was pH dependent and occurred most rapidly below pH 5.0 and led to loss of POD activity.…”
Section: Substrate Specificitysupporting
confidence: 94%
“…The pH optima cPOD-I and rPOD-II were therefore thought to be suitable for the environment in which they are localized. Our result was nearly similar to that reported for POD isoenzymes in Korean radish at pH 5.0 and 6.5 [48] and wheat germ at pH 5.3 and 6.3 [65] but slightly higher than POD in potato tuber sprouts at 4.0 [52], red pepper at 4.5 [66], marula fruit at 4.0 [67], and broccoli at pH 4.0 [4]. However, Lopez and Burgos [68] reported that the release of the heme group from the enzyme active site was pH dependent and occurred most rapidly below pH 5.0 and led to loss of POD activity.…”
Section: Substrate Specificitysupporting
confidence: 94%
“…Four different cationic and a neutralJanionic POD fractions were extracted from barley and partially purified as previously described (Billaud et al 1999). Briefly, POD from 10 g of ground barley was extracted with 50 mL 0.1 M phosphate buffer (pH 7.0) and purified by successively using ammonium sulfate treatment, ion-exchange and hydrophobic chromatographies.…”
Section: Enzyme Sourcementioning
confidence: 99%
“…In both assay conditions, resulting activities were compared with responses versus the guaiacolM,O, system for which optimal conditions have been previously reported (Billaud et al 1999). POD activity was given either in pkat i.e., pmoles H202 consumed s-' x d-' enzymatic extract and expressed as the ratio phenolic compoundguaiacol or in % relative to maximum activity.…”
Section: Standardized Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are reports showing that the optimum pH of POD varies; for example, it is pH 5.0 for bitter gourd [35] and pH 7.0 for Raphanus sativus [36] and between pH 5.3-6.3 for wheat germ. [37] Optimum temperature profile and thermal stability For determination of thermal and storage stability, POD activities were measured at different temperatures. As shown in Figure 3C, POD was stable at 10 and 20°C and showed highest activity at 30 o C. After that point, the enzymatic activity was gradually lost at 40°C and no activity was detected at 50 and 60°C ( Figure 3C).…”
Section: Molecular Weight and Puritymentioning
confidence: 99%